University Students' Knowledge and Perceptions About Concepts, Recommendations, and Health Effects of Added Sugars - Santana, Isabela Paz; Scapin, Tailane; Rodrigues, Vanessa Mello; Bernardo, Greyce Luci; Uggioni, Paula Lazzarin; Fernandes, Ana Carolina; Proença, Rossana Pacheco da Costa (Frontiers in Nutrition, 2022)
It is recommended to limit added sugars to below 10% of the daily energy intake, as excessive consumption has been associated with several chronic non-communicable diseases. This exploratory qualitative study used focus groups to investigate the knowledge and perception of Brazilian university students about added sugars concepts, consumption recommendations, and health effects. Focus groups were led by a moderator using a semi-structured discussion guide. The focus groups were recorded, transcribed verbatim, and subjected to thematic analysis. Five focus groups were conducted with a total of 32 participants (50% women, mean age 23 years). Participants could not distinguish added sugars from sugars naturally present in foods and were unaware of the health impacts associated with excessive added sugar consumption, except for the risk of diabetes. Although most participants reported limiting sugar consumption, they had no knowledge of official consumption recommendations. Given that current public policy agendas aim to reduce added sugar intake, there is a need to strengthen strategies for disseminating information on added sugar concepts, recommendations, health effects and how to identify them in the foods products.